2020
DOI: 10.1177/0363546520946056
|View full text |Cite
|
Sign up to set email alerts
|

Bifactor Model of the Sport Concussion Assessment Tool Symptom Checklist: Replication and Invariance Across Time in the CARE Consortium Sample

Abstract: Background: Identifying separate dimensions of concussion symptoms may inform a precision medicine approach to treatment. It was previously reported that a bifactor model identified distinct acute postconcussion symptom dimensions. Purpose: To replicate previous findings of a bifactor structure of concussion symptoms in the Concussion Assessment Research and Education (CARE) Consortium sample, examine measurement invariance from pre- to postinjury, and evaluate whether factors are associated with other clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 56 publications
2
24
2
Order By: Relevance
“…Contrary to Brett et al who identified a headache factor (headache and pressure in head) and a sensory factor (sensitivity to light and sensitivity to noise), these 4 symptoms (headache, pressure in head, sensitivity to light, and sensitivity to noise) were all loaded on the Migrainous factor in the current investigation. In addition, the Vestibulo-Ocular factor (4 symptoms) and the Energy factor (5 symptoms) in the current investigation were more encompassing than the vestibulo-ocular factor (3 symptoms) and fatigue factor (2 symptoms) reported by Brett et al 13 It has been assumed that energy-related symptoms (eg, fatigue) are closely associated with the acute period after injury, during which physical and cognitive rest are recommended. 34 However, the emergence of the Energy factor as the largest contributor to variance (17%) in a sample of adolescents seen up to 30 days since the injury underscores the importance of using a graded and individually dosed rehabilitation approach throughout recovery and the importance of specifically inquiring about and clinically addressing these items.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Contrary to Brett et al who identified a headache factor (headache and pressure in head) and a sensory factor (sensitivity to light and sensitivity to noise), these 4 symptoms (headache, pressure in head, sensitivity to light, and sensitivity to noise) were all loaded on the Migrainous factor in the current investigation. In addition, the Vestibulo-Ocular factor (4 symptoms) and the Energy factor (5 symptoms) in the current investigation were more encompassing than the vestibulo-ocular factor (3 symptoms) and fatigue factor (2 symptoms) reported by Brett et al 13 It has been assumed that energy-related symptoms (eg, fatigue) are closely associated with the acute period after injury, during which physical and cognitive rest are recommended. 34 However, the emergence of the Energy factor as the largest contributor to variance (17%) in a sample of adolescents seen up to 30 days since the injury underscores the importance of using a graded and individually dosed rehabilitation approach throughout recovery and the importance of specifically inquiring about and clinically addressing these items.…”
Section: Discussioncontrasting
confidence: 45%
“…It is noteworthy to mention that neck pain and trouble falling asleep did not meet the loading criteria on any of the identified factors in the model and therefore were not considered in the 5-factor model, which is consistent with what is previously reported in adults. 13 The failure of neck pain to meet the loading criteria is not surprising considering that neck pain may result from a co-occurring neck injury (eg, whiplash) as opposed to being directly attributable to concussion. 15,45 Similarly, trouble falling asleep did not meet the loading criteria on any of the identified factors that may be explained by the more stringent sleep query in the SCAT5 symptom checklist as opposed to other postconcussive symptom inventories previously used for factor analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, the clinicians performed the GSC with the athlete, and the research team only had access to the total score (total number of symptoms and symptom burden); thus, assessment of individual symptoms (e.g., dizziness, difficulty concentrating, etc.) could not be performed and symptom reporting can be confounded by numerous considerations (49,50). All participants herein were medically managed by the same athletic training and team physician staff using the same concussion management protocol; however, individual management practices and participant experiences/expectations could influence the outcomes of the study.…”
Section: Discussionmentioning
confidence: 99%